PENGARUH PEMBERIAN POSISI ORTHOPNEIC TERHADAP SATURASI OKSIGEN, RESPIRATION RATE DAN FATIGUE PADA PASIEN CONGESTIVE HEART FAILURE DI INSTALASI GAWAT DARURAT - Tanujiarso, Bagus Ananta; Santoso, Bagus; Wulansari, Ni Made Ayu (NHM PRESS, 2025)
Structural and functional abnormalities of the heart cause congestive heart failure (CHF), a clinical syndrome. CHF is characterized by a reduced ability of the heart to pump blood so that the resulting cardiac outputis inadequate which affects hemodynamics such as oxygen saturation and respiratory rate as well as complaints of fatigue. In CHF patients, position adjustment affects respiration rate, oxygen saturation, and shortness of breath. The study aims to determine the effect of orthopneic positioning on oxygen saturation, respiration rate, and fatigue in patients with CHF in IGD. This research was quantitative study with a pre experiment one group pretest posstest design approach. The sample in this study consisted of 32 respondents with quota sampling. The Wilcoxon rank test obtained a p-value <0,001, indicating the influence of orthopneic position on patients with CHF in the emergency care unit. Following the prescribed orthopneic position, the oxygen saturation value increased to 96.50%, the respiration rate increased to 21.75 times/min, and the fatigue rate remained moderate. These results demonstrate that orthopneic positions can effectively alleviate breathing difficulties and fatigue in patients with CHF because in this position it can improve respiratory muscle function and maximize the process of inspiration and expiration. The researcher suggests the implementation of orthopneic positions as an alternative to addressing problems of oxygen saturation, respiration rate, and fatigue in patients with CHF in the emergency care facility.